1976
DOI: 10.1021/bi00661a020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the association of specific proteins with messenger ribonucleic acid

Abstract: Isolation of messenger ribonucleic acid (mRNA)-protein particles from cytosol or dissociated polyribosomes yielded complexes in which several proteins were consistently associated with mRNA. Some of the mRNA-associated proteins appeared to have a high affinity for mRNA since they remained complexed to mRNA during centrifugation in CsCl gradients. Quantitation of RNA and protein in polyribosomal mRNPs suggested that each molecule of mRNA bound a molecule of each of the two major proteins of 78 000 and 52 000 ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 37 publications
3
19
1
Order By: Relevance
“…Last, concerning rabbit reticulocyte free cytoplasmic messenger ribonucleoproteins, Barrieux et al [46] also found multiple bands on dodecylsulfate/ acrylamide gel (see also Results). On the contrary, Baglioni [Sl] found only two proteins, which are identical to the ones in polysomal messenger ribonucleoprotein.…”
Section: The Proteins In the Free Cytoplasmic Messenger Rihonucleopromentioning
confidence: 78%
See 2 more Smart Citations
“…Last, concerning rabbit reticulocyte free cytoplasmic messenger ribonucleoproteins, Barrieux et al [46] also found multiple bands on dodecylsulfate/ acrylamide gel (see also Results). On the contrary, Baglioni [Sl] found only two proteins, which are identical to the ones in polysomal messenger ribonucleoprotein.…”
Section: The Proteins In the Free Cytoplasmic Messenger Rihonucleopromentioning
confidence: 78%
“…One is to analyse the proteins bound to a mixture of different species of mRNA from a type of cell known to synthesize different kinds of proteins (e.g. Ehrlich ascites [46], HeLa [34]). In this case one may expect that the proteins common to most ribonucleoproteins would emerge, whereas proteins specific to individual mRNA would not be seen.…”
Section: The Proteins In the Free Cytoplasmic Messenger Rihonucleopromentioning
confidence: 99%
See 1 more Smart Citation
“…Not only are there differences in the complexity of mRNP proteins [6, 311 but also in the protein:RNA ratio between the two classes. For instance, ratios of 0.5 and 4.0 were determined for mRNPs, washed with 0.5 M KC1, from polysomal and subribosomal fractions in ascites cells [16]. The properties of oocyte mRNP particles described here differ from those of polysomal mRNPs in several respects.…”
Section: Discussionmentioning
confidence: 90%
“…As a DNAbinding protein, YB-1 binds to promoters containing the Y box element and either activates or represses gene expression (23,48,54,77). As an mRNA-binding protein, YB-1 is the most abundant protein of messenger ribonucleoprotein particles (mRNPs) and controls translation in a dose-dependent fashion (9,12,49). Low concentrations stimulate translation, and higher ones are inhibitory.…”
mentioning
confidence: 99%